A clinical study to measure anti‐erosion properties of a stabilized stannous fluoride dentifrice relative to a sodium fluoride/triclosan dentifrice. Issue 2 (22nd June 2015) - West, NX; Seong, J; Hellin, N; Eynon, H; Barker, ML; He, T
Abstract: Objective: To compare the enamel protection efficacy of a stabilized stannous fluoride (SnF2 ) dentifrice to a sodium fluoride (NaF)/triclosan dentifrice following acidic erosive challenge. Methods: In this in situ, randomized, controlled, double‐blind, two‐treatment, four‐period crossover clinical trial, subjects wore an appliance fitted with human enamel samples 6 h day −1 during each 15‐day treatment period. Twice each treatment day they swished with their assigned dentifrice slurry: 0.454% SnF2 /0.077% NaF or 0.32% NaF/0.3% triclosan. After each treatment and two other times daily, subjects swished with 250 ml of orange juice over a 10‐min period (acidic erosive challenge). Enamel samples were measured for tooth surface loss using contact profilometry at baseline and days 10 and 15. Results: Thirty‐six subjects (mean age 44.8 years, range 23–65 years) were randomized to treatment; 33 subjects completed the final study visit. There were no statistically significant baseline differences ( P  > 0.44) in the specimen surfaces of the two dentifrice treatment groups via profilometry. At day 10, the SnF2 dentifrice provided a statistically significant ( P  < 0.0001) reduction in enamel loss by 67% versus the NaF/triclosan dentifrice with estimated medians of 1.22 and 3.68 μm, respectively. At day 15, the SnF2 dentifrice again provided a significantly greater benefit ( P  < 0.0001) against tooth surface loss versus the NaF/triclosan dentifrice, with 68% less erosion, and estimated medians of 1.60 and 5.03 μm, respectively. Both dentifrices were well tolerated. Conclusion: A stabilized SnF2 dentifrice provided superior protection against the initiation and progression of tooth enamel surface loss in situ after erosive challenge compared to a NaF/triclosan dentifrice.